The Role of Research Methodology in Counsellor Education: A Case of Second-Order Effects - Barak, Azy (Canadian Journal of Counselling and Psychotherapy, 2007)
Research methodology training within counsellor education has consistently been advocated for various reasons, all of which are related to research understanding and applications within the counselling context. The current view proposes that there is additional critical value for training in research in that-it promotes the development of counsellors' cognitive operations relevant for their actual counselling conduct (such as critical thinking, self-awareness to own biases, or doubting evidence and the obvious) by means of second-order effects. It is suggested that different components of a research methodology education should thus be emphasized in order to further foster counsellor in-session cognitive functioning.